Pregnancy and Childbirth Experiences of Women with Epilepsy: A Phenomenological Approach - Woo Joung Joung (Elsevier, 2019)
Purpose: This study sought to understand and describe the pregnancy and childbirth experiences of women with epilepsy (WWE). Methods: Data were collected from 2016-2017 through in-depth individual interviews with 12 WWE who experienced childbirth within 36 months. Verbatim transcripts were analyzed following Colaizzi's phenomenological analysis to uncover the meaning of the experiences of the participants. Results: The pregnancy and childbirth experiences of WWE were clustered into four theme clusters and 8 themes from 20 meaning units: 1) Feeling anxious due to unplanned pregnancy and unexpected changes; 2) Standing at crossroads that never guarantee satisfaction; 3) Carrying a burden of fearful expectation and daily routines; 4) Enjoying rewards of pregnancy and childbirth as a woman with epilepsy. Conclusion: WWE had strong anxiety about the possible abnormality of their babies during pregnancy. They had mixed feelings about delivery and had to make a tough decision about breastfeeding because of antiepileptic drugs use. After childbirth, they had increased fear about the possible inheritance of the illness and had a hard time managing the burden of childcare and seizure control. However, pregnancy allows these women to gain disease awareness and further appreciate the importance of their health. The study results indicate the need for multidisciplinary intervention for WWE, before, during, and after pregnancy to increase communication with health professionals. Especially, preconception counselling and education led by nurses are required. Keywords: epilepsy, pregnancy, qualitative research, woman